2011
DOI: 10.1007/s00535-011-0472-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term administration of PPI reduces treatment failures after esophageal variceal band ligation: a randomized, controlled trial

Abstract: Long-term administration of PPIs reduced the risk of treatment failure after EVL. Acid suppression therapy should also be considered as a treatment option after EVL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 21 publications
4
54
2
Order By: Relevance
“…Nijhawan et al observed that 60% of post-EVL ulcers were healed within 2 weeks and 100% were healed within 3 weeks [26]. Although numerous studies demonstrate that PPIs effectively reduce post-procedure ulcer size and accelerate ulcer healing, none have demonstrated altered rebleeding or mortality rates in patients with post-treatment EV bleeding [15–17, 27]. The explanation provided was that most rebleeding events arise from varices rather than ulcers, and therefore the value of PPI use was questioned.…”
Section: Discussionmentioning
confidence: 99%
“…Nijhawan et al observed that 60% of post-EVL ulcers were healed within 2 weeks and 100% were healed within 3 weeks [26]. Although numerous studies demonstrate that PPIs effectively reduce post-procedure ulcer size and accelerate ulcer healing, none have demonstrated altered rebleeding or mortality rates in patients with post-treatment EV bleeding [15–17, 27]. The explanation provided was that most rebleeding events arise from varices rather than ulcers, and therefore the value of PPI use was questioned.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Tzathas et al [37], the authors suggested that H. pylori eradication does not protect all cirrhotics from ulcer recurrence and the majority of ulcers recur in H. pylori negative patients; therefore, omeprazole maintenance treatment is mandatory, irrespectively of H. pylori status. In addition there are data to support acid suppression therapy in the treatment of post-banding ulcers [8,38]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the subjects (n = 21 and 22 in the rabeprazole and placebo groups, respectively) were included only after endoscopic statement of post-EVL ulcer healing; so the PPI effect on active post-banding ulcers was not evaluated. [31] In 2013, another randomized controlled study compared 5 days of intravenous PPI (pantoprazole 40 mg or omeprazole 40 mg) versus intravenous vasoconstrictors (somatostatin 250 mg/h or terlipressin 1 mg/6 h) after EVL in 118 individuals with cirrhosis and acute variceal bleeding. The number and the width of the esophageal ulcers were higher in the vasoconstrictor group than in the PPI group, but no significant difference in esophageal ulcer bleeding was found between the treatments.…”
Section: Risk Factorsmentioning
confidence: 99%